2008
DOI: 10.1038/nmeth.1202
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell photoactivated localization microscopy of nanoscale adhesion dynamics

Abstract: We demonstrate live-cell super-resolution imaging using photoactivated localization microscopy (PALM). The use of photon-tolerant cell lines in combination with the high resolution and molecular sensitivity of PALM permitted us to investigate the nanoscale dynamics within individual adhesion complexes (ACs) in living cells under physiological conditions for as long as 25 min, with half of the time spent collecting the PALM images at spatial resolutions down to ~60 nm and frame rates as short as 25 s. We visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
749
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 814 publications
(765 citation statements)
references
References 15 publications
12
749
1
3
Order By: Relevance
“…When the product of this fraction and the density of fluorescent labels reaches approximately one fluorophore per diffraction-limited volume, it becomes difficult to resolve and precisely localize the activated fluorophores. Hence the on-off ratio limits the density of fluorescent labels that can be localized, which in turn affects the effective image resolution based on the Nyquist sampling theorem (10). (iii) The third property is the dimerization tendency.…”
mentioning
confidence: 99%
“…When the product of this fraction and the density of fluorescent labels reaches approximately one fluorophore per diffraction-limited volume, it becomes difficult to resolve and precisely localize the activated fluorophores. Hence the on-off ratio limits the density of fluorescent labels that can be localized, which in turn affects the effective image resolution based on the Nyquist sampling theorem (10). (iii) The third property is the dimerization tendency.…”
mentioning
confidence: 99%
“…It has been further demonstrated that many conventional dyes can be used for super-resolution imaging based on photoswitching/bleaching and localization of single molecules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Using single-molecule-based super-resolution methods, 3D resolutions down to approximately 10 nm have been demonstrated for fixed samples (21)(22)(23)(24)(25)(26), and live-cell imaging has also been achieved with spatial resolutions of 20-60 nm at time resolutions ranging from 0.5 s to 1 min (27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…However, membrane proteins are often not distributed uniformly on the membrane, but instead form localized domains nonideal for general membrane imaging. Moreover, since probe density is a key determinant of the image resolution (27,31), protein labels need to be expressed at high levels to achieve high resolutions, which can cause overexpression artifacts. An alternative to protein labels is small-molecule probes that directly bind to membrane structures, which have been widely used for specific labeling of membrane organelles (33).…”
mentioning
confidence: 99%
“…Finally, the third aspect of imaging that needs to be addressed is resolution, where we find great efforts directed towards super-resolution techniques, including stimulated emission depletion (STED) [63][64][65][66], structured illumination microscopy (SIM) [67,68], photoactivated localization microscopy (PALM) [69,70], and stochastic optical reconstruction microscopy (STORM) [71][72][73][74]. These approaches offer sub-diffraction-limited resolution and have opened new ways of exploring the submicron world within the living cell.…”
Section: Imaging Smaller: Pushing Resolution To the Limitmentioning
confidence: 99%